Perancangan Produk Interior Perpustakaan Anak Gereja Kristen Indonesia Merisi Indah di Surabaya - Paul John Kalampung; Andereas Pandu Setiawan; Grace Setiati Kattu (Intra, 2020)
The Merisi Indah Indonesian Christian Church (GKI) Building was built and inaugurated in July 2019 is used for Sunday school children. This Sunday school building contains the need of rooms and furnishings such as libraries and playgrounds with enough books and toys which may server the children well while they are waiting for their parents. The important thing of this project is that the requirements per room are specific and the types of use of furniture are mainly built to support the Sunday School Studies. All items in the commission building should not be pinned, nailed and suggested that the weight of the furniture is not excessive. Based on the background above, it will be designed in the form of making bookshelves, toy shelves, and banner and chalkboard holders. In this design, multiplex, Dutch teak, iron and hollow steel are chosen. The product has the